NOSTALGIA FOR THE NEW: VIDEO GAME "REMAKES" AND THE LIMITS OF REFLECTION - Neill Hoch, Indira (AoIR Selected Papers of Internet Research, 2020)
In this paper I consider comments posted on the official trailers of Final Fantasy VII Remake and Yakuza Kiwami (from the verified Playstation YouTube channel) as iterations of nostalgia within the context of fifth- and sixth-generation digital game “remakes,” where the narrative and characters (Mäyrä’s (2008) “shell”) of the original game have been retained, but the game’s engine and mechanics (Mäyrä’s “core”) have been wholly replaced with modern technology. Using these comments, I attempt to place responses to these games into Garda’s (2013) nostalgia continuum as a way of testing the possibilities and limitations of “nostalgia” as a framework for understanding AAA remakes.